2019
DOI: 10.1111/apa.14881
|View full text |Cite
|
Sign up to set email alerts
|

Shared unmeasured characteristics among siblings confound the association of Apgar score with stress resilience in adolescence

Abstract: AimWe investigated the association between low Apgar score, other perinatal characteristics and low stress resilience in adolescence. A within‐siblings analysis was used to tackle unmeasured shared familial confounding.MethodsWe used a national cohort of 527 763 males born in Sweden between 1973 and 1992 who undertook military conscription assessments at mean age of 18 years (17–20). Conscription examinations included a measure of stress resilience. Information on Apgar score and other perinatal characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This study used a register-based cohort described in greater detail elsewhere, 5 comprising males born between 1970 and 1992, included in the Swedish Military Conscription Register between ages 16 and 20 years. A total of 896,696 men were identified and 152,148 were excluded due to Swedish personal identification number errors (2166), conscription examination after age of 20 years (6747), an MS diagnosis before age of 20 years (32), death or emigration before age of 20 years (9,443), BMI ⩽ 15 (157), and missing information for age at conscription (58), socioeconomic characteristics (13,719), and height and weight (119,826).…”
Section: Methodsmentioning
confidence: 99%
“…This study used a register-based cohort described in greater detail elsewhere, 5 comprising males born between 1970 and 1992, included in the Swedish Military Conscription Register between ages 16 and 20 years. A total of 896,696 men were identified and 152,148 were excluded due to Swedish personal identification number errors (2166), conscription examination after age of 20 years (6747), an MS diagnosis before age of 20 years (32), death or emigration before age of 20 years (9,443), BMI ⩽ 15 (157), and missing information for age at conscription (58), socioeconomic characteristics (13,719), and height and weight (119,826).…”
Section: Methodsmentioning
confidence: 99%
“…9 However, there is no clear definition how neonates with scores of 6 are clinically different from neonates with scores of 7. Further, researchers often arbitrarily create their own cut-off of normal/abnormal or score groupings to allow for statistical analysis, [48][49][50] which complicates comparisons of study outcomes and introduces bias.…”
Section: Discussionmentioning
confidence: 99%
“…It is not implausible that the observed association between preterm birth and stress-related disorders is explained by genetic factors that may influence both outcomes. It has been reported that low 5 min Apgar score is associated with less stress resilience in young adulthood [51]. Although the Apgar score can be seen as a proxy to many parental and perinatal conditions, the heritability is estimated to be 42% [52].…”
Section: Discussionmentioning
confidence: 99%